Causes of East Asian Temperature Multidecadal Variability Since 850 CE. Issue 24 (29th December 2018) - Wang, Jianglin; Yang, Bao; Osborn, Timothy J.; Ljungqvist, Fredrik Charpentier; Zhang, Huan; Luterbacher, Jürg
Abstract: The drivers of multidecadal‐ to centennial‐scale variability in East Asian temperature, apparent in temperature reconstructions, are poorly understood. Here we apply a multivariate regression analysis to distinguish the influences of large‐scale modes of internal variability (Atlantic Multidecadal Oscillation and Pacific Multidecadal Oscillation) and external natural (orbital, solar, and volcanic) and anthropogenic (greenhouse gas concentrations, aerosols, and land use changes) forcings on East Asian warm‐season temperature over the period 850–1999 CE (Common Era). We find that ~80% of the temperature change on time scales longer than 30 years can be explained including all drivers over the full‐length period. The Pacific Multidecadal Oscillation was the most important driver of multidecadal temperature variability during the Medieval Climate Anomaly (here 950–1250), while solar contribution was important during the Little Ice Age (here 1350–1850). Since 1850, two thirds of temperature change can be explained with anthropogenic forcing, whereas one third was related mainly to the Atlantic Multidecadal Oscillation and volcanic forcing. Plain Language Summary: The Atlantic Multidecadal Oscillation (AMO) and Pacific Multidecadal Oscillation (PMO) are suggested to be key components of internal temperature variability globally and in the Northern Hemisphere. However, the contribution of the AMO and PMO to temperature at regional/continental scales in preindustrial times is still unclear. Here we use a multivariate regression analysis to distinguish the AMO and PMO contributions to the East Asian temperature multidecadal (> 30 years) changes from the influence of external (orbital solar, volcanic, and anthropogenic) forcings. We find that the contribution of the AMO and PMO is of similar magnitude as solar and volcanic forcing during the period 850–1999 CE (Common Era). We apply the same approach to three subperiods and find that the PMO, solar forcing, and anthropogenic forcing contributed most during the periods 950–1250, 1350–1850, and 1850–1999, respectively. Key Points: Atlantic and Pacific Multidecadal Oscillations (AMO and PMO) are important contributors to East Asian temperature variability The combined contribution of the AMO and PMO is of similar magnitude as solar and volcanic forcing during 850–1999 The most important drivers change between subperiods: for 950–1250 it is the PMO, and for 1350–1850 it is solar forcing